2019
DOI: 10.3390/rs11040428
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Validation of the Time-Varying Characteristic for the GPS Differential Code Bias

Abstract: The time-varying characteristic of the bias in the GPS code observation is investigated using triple-frequency observations. The method for estimating the combined code bias is presented and the twelve-month (1 January–31 December 2016) triple-frequency GPS data set from 114 International GNSS Service (IGS) stations is processed to analyze the characteristic of the combined code bias. The results show that the main periods of the combined code bias are 12, 8, 6, 4, 4.8 and 2.67 h. The time-varying characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…To enhance IFCB estimation, the constant part of the GPS IFCB is computed with pseudorange observations [21]. Meanwhile, it has been reported that the GPS pseudorange observation-based IFCB is a combination of satellite DCB(P1-P2) and DCB(P1-P5), while the GPS carrier phasebased IFCB is the combined uncalibrated phase delay [22]:…”
Section: Introductionmentioning
confidence: 99%
“…To enhance IFCB estimation, the constant part of the GPS IFCB is computed with pseudorange observations [21]. Meanwhile, it has been reported that the GPS pseudorange observation-based IFCB is a combination of satellite DCB(P1-P2) and DCB(P1-P5), while the GPS carrier phasebased IFCB is the combined uncalibrated phase delay [22]:…”
Section: Introductionmentioning
confidence: 99%
“…DCBs occur because of hardware imperfections inside receivers and satellites, and are contained in GNSS receiver observations [ 1 ]. However, DCBs must be known for GNSS applications, such as total electron content (TEC) determination, which derives TEC from receiver observations [ 2 , 3 , 4 ]. DCBs can cause errors of several meters in TEC estimates if they are ignored and can even result in negative ionospheric delay values [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They reported an agreement with the global ionospheric map (GIM) data with a mean difference of less than 0.7 ns (~2 TECU) and an RMS of less than 0.4 ns (~1 TECU). Li et al [ 17 ] analyzed triple-frequency combinations and proved that the real satellite DCBs are time-varying. Wang et al [ 18 ] mitigated variations in DCB by separating DCB from ambiguity.…”
Section: Introductionmentioning
confidence: 99%